Current Changes in Primary Education: The issue of "different" in a primary school mathematics classroom - Ioannis Papadopoulos; Darina Jirotková; Jana Slezáková; Esperanza López Centella (Charles University, 2020)
In the setting of the transformation of our societies to become multicultural ones, we intend in this paper to examine situations in a mathematics classroom where respect for, and exclusion of, the 'different' co-exist. Conducting an instrumental case study, we follow two Grade 4 groups while they are solving a mathematics generalization task. We examine how the interaction that took place between the members of the teams mirrors the two faces of the same coin (i.e. the culture of the classroom) and at the same time reflects the change in the primary classroom that necessitates openness and genuine respect for the 'different'. On the one hand, we will demonstrate the dynamic of the harmony that was apparent between the members of one of the groups since the 'different' was not a barrier but a source of mathematical ideas that contributed to the solution. On the other hand, the lack of openness in the other group resulted in good opportunities for 'doing mathematics' being missed and put the self-confidence of one of its members at risk. Keywords: classroom diversity and conflict, multicultural mathematics classroom, collaborative problem-solving